Analisis Value Chain Untuk Menciptakan Strategi Bersaing Dalam Industri Semen - , Alfin Kurniadi, S. T, Dr. Fahmy Radhi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Cement industry in Indonesia is oligopolistic nowadays with the characteristics of the tight price competition among cement producers. To cope with this situation, companies have to survive in the competitive price or innovate by creating the competitive advantage. The creation of competitive advantage can be identified from the observation of value chain in the company's activities, whether it is in accordance with the standards established by the company or not and whether it has provided the competitive advantage to the company or not. This study is aimed at analyzing how PT Holcim Indonesia copes with the oligopistic market competition which is based on price competition. The analysis was conducted by observing the companyâs value chain activities, whether they have been in accordance with the established standards or not